EDUKASI HIPERTENSI DAN DIABETES MELITUS DI KAMPUNG JENGGALU KITO BENGKULU: EDUCATION ON HYPERTENSION AND DIABETES MELLITUS IN KAMPUNG JENGGALU KITO, BENGKULU - Anisa Tifani Maulidyanti; Mika Oktarina; Choralina Eliagita; Nuril Absari (LPPM Universitas Abdurrab, 2025)
Non-communicable diseases, hypertension and diabetes mellitus, show an increasing trend in Indonesia. In the population aged 18 years and over, the prevalence of hypertension increased from 25.8% to 34.1%, while the prevalence of diabetes mellitus increased from 6.9% to 10.9%. This community service activity aims to increase public knowledge and awareness of hypertension and diabetes mellitus, as well as to monitor blood sugar levels and blood pressure in residents of Jenggalu Kito Village, Bengkulu City. The service method is through a health education approach in the form of socialization, discussion, and blood pressure checks and Random Blood Sugar (GDS) checks. Participants numbered 20 people in the adult age group in Jenggalu Kito Village. Of the 20 people who underwent the examination, it was found that 13 people had hypertension and 10 people were indicated to have diabetes mellitus. Pre-tests and post-tests were conducted to measure the increase in participants' knowledge about hypertension and diabetes mellitus. The results of this activity showed a significant increase in participants' understanding, indicated by an average post-test result that was higher than the pre-test, thus indicating the success of the education. The conclusion and suggestion of this community service is because this program has succeeded in increasing knowledge about the management of Hypertension and Diabetes Mellitus in patients. It is recommended that similar activities be carried out continuously in order to increase public awareness and understanding in efforts to prevent and overcome hypertension and diabetes mellitus.